Design your own anime and manga characters : step-by-step lessons for creating and drawing unique characters : learn anatomy, poses, expressions, costumes, and more /: step-by-step lessons for creating and drawing unique characters : learn anatomy, poses, expressions, costumes, and more. (2022) - Choi, T. B
No abstract available